Coronary Artery Disease and Gallbladder Inflammatory Pseudopolyps - Margherita Fosio; Giulia Cherobin; Roberto Stramare; Matteo Fassan; Chiara Giraudo (Diagnostics, 2022)
Axial MR image demonstrating multiple small gallbladder polypoid lesions characterized by contrast enhancement in a 78-year-old male hospitalized for acute chest pain due to coronary artery disease who showed fever and emesis during hospitalization and had signs of acute acalculous cholecystitis at computed tomography. Given the overall clinical conditions and the MR features, the inflammatory origin of the polyps was considered. The patient underwent cholecystectomy and the histological diagnosis of gallbladder inflammatory pseudopolyps was confirmed. This rare entity represents 5–10% of all gallbladder polyps, and their differentiation from benign and malignant tumors might be challenging especially in acalculous patients, thus surgery is often performed.